An algorithm for reducing complexity in parametric predictive control - Rossiter, J. A.; Kouvaritakis, B.; Cannon, M. (International journal of control, 2005)
Multi parametric quadratic programming solutions to predictive control can require large numbers of regions which would make practical implementation difficult. This paper demonstrates how an underexplored prediction class can be combined with parametric programming to give far simpler solutions and at little cost to optimality. The key proposal is to explore how one can give more flexibility in the shape of the predictions without increasing the required numbers of degrees of freedom; this flexibility allows terminal regions to be enlarged.